Broccoli Florets Supplementation Improves Insulin Sensitivity and Alters Gut Microbiome Population—A Steatosis Mice Model Induced by High-Fat Diet - Zandani, Gil; Anavi-Cohen, Sarit; Tsybina-Shimshilashvili, Nina; Sela, Noa; Nyska, Abraham; Madar, Zecharia (Frontiers in Nutrition, 2021)
Non-alcoholic fatty liver disease (NAFLD) is linked to obesity, type 2 diabetes, hyperlipidemia, and gut dysbiosis. Gut microbiota profoundly affect the host energy homeostasis, which in turn are affected by a high-fat diet (HFD) through the liver-gut axis, among others. Broccoli contains beneficial bioactive compounds and may protect against several diseases. This study aimed to determine the effects of broccoli supplementation to a HFD on metabolic parameters and gut microbiome in mice. Male (7-8 weeks-old) C57BL/J6 mice were fed a standard or a HFD with or without 10% broccoli florets/stalks for 17 weeks. Liver histology and serum biochemical factors were evaluated. Alterations in protein and gene expression of key players in lipid and carbohydrate metabolism as well as in gut microbiota alterations were also investigated. Broccoli florets significantly reduced serum insulin levels, HOMA-IR index, and upregulated adiponectin receptor expression, but did not affect fat accumulation, carbohydrate or lipid metabolism-related parameters. Modifications in diversity and in microbial structure of proteobacteria strains, Akermansia muciniphila and Mucispirillum schaedleri were observed in the broccoli supplemented HFD-fed mice. The present study suggests that dietary broccoli alters parameters related to insulin sensitivity and modulates the intestinal environment. More studies are needed to confirm this study's results and to investigate the mechanisms underlying these beneficial effects.